Um estudo sobre as modificações corporais pela via das cirurgias plásticas como manifestação do traço perveso em mulheres midiáticas - Silva, Raquel de Souza Gomes da (2015)
The body modification is increasing among women who search for plastic surgery and other aesthetic procedures in order to achieve a body that is praised by the media. Some of them modify their bodies beyond measure pulling their floating ribs out to make their waists slimmer, performing many procedures at the same time or when they exceed the amount of silicon implant in their breasts which detonates an undue behavior guideded by the disproportion. However, the current context is marked by a perverse social organization because it sets itself on the boundaries deletion and on the elation of the jouissance and moves the appearance of perverse traces independently on the clinical structure. Thus, this study aims to highlight some perverse traces in three cases of media women that compulsively change their bodies. We ve collected the depositions displayed on internet videos, focusing on those who dealt with the aesthetic procedures. For analysis, we ve selected three perverse traces: disproportion and the boundaries transgression, the partial objects fixation, the body as a fetish and the search for other people s look as way to achieve jouissance. Those women through the disproportion , deny their lacks by offering their bodies, in parts, as a fetish object to the others look.